Lactate and base deficit are predictors of mortality in critically ill patients with cancer - Hajjar, Ludhmila Abrahão (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVE: Cancer patients frequently require admission to intensive care unit. However, there are a few data regarding predictive factors for mortality in this group of patients. The aim of this study was to evaluate whether arterial lactate or standard base deficit on admission and after 24 hours can predict mortality for patients with cancer. METHODS: We evaluated 1,129 patients with severe sepsis, septic shock, or postoperative after high-risk surgery. Lactate and standard base deficit collected at admission and after 24 hours were compared between survivors and non-survivors. We evaluated whether these perfusion markers are independent predictors of mortality. RESULTS: There were 854 hospital survivors (76.5%). 24 h lactate >1.9 mmol/L and standard base deficit < -2.3 were independent predictors of intensive care unit mortality. 24 h lactate >1.9 mmol/L and 24 h standard base deficit < -2.3 mmol/Lwere independent predictors of hospital death. CONCLUSION: Our findings suggest that lactate and standard base deficit measurement should be included in the routine assessment of patients with cancer admitted to the intensive care unit with sepsis, septic shock or after high-risk surgery. These markers may be useful in the adequate allocation of resources in this population.